Real‐Time Monitoring of Enzyme‐Catalysed Reactions using Deep UV Resonance Raman Spectroscopy. Issue 29 (2nd May 2017) - Westley, Chloe; Fisk, Heidi; Xu, Yun; Hollywood, Katherine A.; Carnell, Andrew J.; Micklefield, Jason; Turner, Nicholas J.; Goodacre, Royston
Abstract: For enzyme‐catalysed biotransformations, continuous in situ detection methods minimise the need for sample manipulation, ultimately leading to more accurate real‐time kinetic determinations of substrate(s) and product(s). We have established for the first time an on‐line, real‐time quantitative approach to monitor simultaneously multiple biotransformations based on UV resonance Raman (UVRR) spectroscopy. To exemplify the generality and versatility of this approach, multiple substrates and enzyme systems were used involving nitrile hydratase (NHase) and xanthine oxidase (XO), both of which are of industrial and biological significance, and incorporate multistep enzymatic conversions. Multivariate data analysis of the UVRR spectra, involving multivariate curve resolution‐alternating least squares (MCR‐ALS), was employed to effect absolute quantification of substrate(s) and product(s); repeated benchmarking of UVRR combined with MCR‐ALS by HPLC confirmed excellent reproducibility. Abstract : Biotransformation : A rapid, UV resonance Raman spectroscopic approach for real‐time reaction monitoring using two different enzyme classes was developed. In combination with chemometrics, substrate(s) and product(s) were quantitatively measured and successfully benchmarked by using HPLC over a four‐week period, thus demonstrating excellent reproducibility (see figure).